Sorption of lead on cementitious materials in presence of organics - Drtinová, Barbora; Kittnerová, Jana; Bergelová, Karolína; Burešová, Marta; Baborová, Lucie (Frontiers in Nuclear Engineering, 2023)
Commercial cementitious material, hydrated cement pastes of type CEM I and CEM III, and a synthetic cementitious phase CSH (calcium-silicate-hydrates) with a Ca/Si ratio equal to 1.0, 1.2, and 1.4 were used in the study of lead sorption. Kinetic and equilibrium experiments were performed under different conditions, namely liquid to solid phase ratio and the presence of organic compounds (EDTA, phthalate). The duration of equilibrium experiments was determined based on kinetic experiments, 1 week for calcium-silicate-hydrates and 3 weeks for hydrated cement paste. Equilibrium experiments were evaluated using the distribution ratio Rd and sorption isotherms. For both hydrated cement pastes, Rd’s in the range 102–103 L kg−1 were found while for calcium-silicate-hydrates the distribution ratio values were an order of magnitude higher under comparable conditions. The difference in the studied cementitious materials was also manifested in the shape of the sorption isotherm, while the behavior of calcium-silicate-hydrates can be fitted linearly and therefore by the Kd-model, for hydrated cement paste as more complex cement material it is necessary to use a non-linear isotherm description. The effect of organic matter, represented here by EDTA and phthalate, described by the sorption reduction factor SRF was more apparent for calcium-silicate-hydrates, where its value was always higher than one and reached up to 500. On the contrary, for hydrated cement paste CEM I and CEM III, all determined SRFs were less than 1.